1991
DOI: 10.1007/bf01973723
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous absorption and metabolism of aldrin by rat skin in diffusion cells

Abstract: Using a static diffusion cell with varying receptor fluids the viability of isolated rat skin mounted as whole skin or as split thickness skin has been studied. Skin viability decreased with time with phosphate buffer or Eagles MEM and was not supported with ethanol/water as the receptor fluid. The pesticide aldrin was absorbed through the skin into ethanol/water but not the aqueous receptor fluids. With viable skin preparations aldrin was metabolised to dieldrin and absorbed aldrin and the metabolite remained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…According to this paper, more than 99% of the epoxidation product, dieldrin, was probably formed locally by dermal metabolism of percutaneously absorbed aldrin. Other papers detecting the metabolism of aldrin to dieldrin by rat skin have also been published in the literature ( , ).…”
Section: Resultsmentioning
confidence: 99%
“…According to this paper, more than 99% of the epoxidation product, dieldrin, was probably formed locally by dermal metabolism of percutaneously absorbed aldrin. Other papers detecting the metabolism of aldrin to dieldrin by rat skin have also been published in the literature ( , ).…”
Section: Resultsmentioning
confidence: 99%
“…Using a rat epidermal membrane, carbaryl applied at 200 nmol cm-2 was absorbed to ethanol/water as receptor fluid; 10% in 5 h. This absorption relates to the recovery observed here of 2.76% through whole rat skin to ethanol/water receptor fluid in 7.5 h. Recovery to receptor fluid was lower with aqueous receptors, but previous work has shown that with saline and Earles MEM tissue culture medium as the receptor fluids, drug metabolising enzymes are relatively well supported within the skin for several hours, although in the presence of 50% ethanol/water the enzyme activity falls off very rapidly (Macpherson et al 1990). These conditions have been shown to support metabolism of aldrin to dieldrin during absorption through the skin (Macpherson et al 1991). Therefore the capacity for carbaryl metabolism was present when aqueous receptors were used, supporting the assumption that insufficient chemical came in contact with the enzymes for metabolism to be detected.…”
Section: Discussionmentioning
confidence: 86%
“…27 The choice of a suitable receptor solution can also be compromised by a need to maintain skin viability. 19 Macpherson et al 30 have reported that the pesticide aldrin is absorbed through skin into ethanol-water but not aqueous receptor fluids. However, skin viability was not supported by an ethanol-water system.…”
Section: Discussionmentioning
confidence: 99%